Studies on the effect of roof insulation on environmental temperature in poultry breeder houses in the tropics. - Oh, B.T.; Kong, K.P.
This paper reports preliminary studies of a 24-hr cyclic environmental temperature pattern in insulated and uninsulated breeder houses in the tropics. The insulated breeder house with extruded polystyrene foam had an ambient temperature of 2.05C lower than the uninsulated house during the hottest part of the day. The mean period of environmental temperature above 30C in the insulated house was between 12.30 and 16.00 hr while in the uninsulated house it was between 11.14 and 17.28 hr. The birds in the insulated house experienced an average 12 hr and 17 min longer heat stress period per day. On a hot day a temperature of as high as 50C was recorded immediately below the asbestos roof. It was concluded that the extruded polystyrene foam was an ideal roofting to reduce excessive heat stress in poultry breeder houses in the tropics.